Pengaruh Pemberian Magnesium Sulfat (MgSO4) Terhadap Kadar Nitric Oxide dan Prostacyclin pada Preeklampsia - Pangkahila, Evert; Kade Yudi Saspriyana; Clara Amanda; Winty Septiani (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction : Preeclampsia is a pregnancy-related syndrome with significant maternal and neonatal risks, affecting 4.6% of pregnancies globally. Its pathophysiology, linked to an imbalance between prostacyclin (a vasodilator) and thromboxane (a vasoconstrictor), remains poorly understood. Magnesium sulfate (MgSO4) is widely used for seizure prophylaxis in preeclampsia, but its effect on nitric oxide (NO) and prostacyclin levels is still debated. Methods: This quasi-experimental study included 30 pregnant women diagnosed with severe preeclampsia. Baseline serum levels of NO and prostacyclin were measured before MgSO4 administration and re-evaluated after 24 hours of treatment. Changes in biomarker levels were assessed using paired t-tests, with a significance threshold of p < 0.05. Results: The mean NO level increased from 35.2 ± 5.6 µmol/L before treatment to 49.8 ± 6.3 µmol/L after MgSO4 administration, showing a statistically significant difference (p < 0.001). Similarly, prostacyclin levels rose from a baseline of 42.1 ± 4.8 pg/mL to 58.7 ± 5.2 pg/mL post-treatment (p < 0.001). These findings suggest a robust enhancement of vasodilatory activity, supporting the role of MgSO4 in improving vascular endothelial function. Conclusion: MgSO4 administration significantly increases NO and prostacyclin levels, demonstrating its efficacy in reducing vascular resistance in preeclamptic pregnancies. These results reinforce its clinical utility, offering a mechanistic insight into its vasodilatory and anti-convulsive properties. Keywords: Preeclampsia, magnesium sulfate, nitric oxide, prostacyclin, vascular biomarkers